Comparison of longitudinal changes in refractive error of hyperopic children with or without refractive accommodative esotropia - Song, Ji Eun; Han, Hyo Ji; Choi, Chul Y.; Khoramnia, Ramin; Chang, Hae Ran; Han, So Young (Diagnostics, 2021)
We investigated longitudinal changes in the spherical equivalent refractive error (SE) in hyperopic children with or without refractive accommodative esotropia (AccET). A total of 456 patients met the inclusion criteria: 190 (41.7%) in the hyperopic control group and 266 (58.3%) in the AccET group. All patients received at least 3 years of follow-up after spectacle prescription. Subgroups were divided according to age when spectacles were prescribed, presence of amblyopia, or initial SE. Longitudinal changes in SE in children with hyperopia showed a gradual decrease, although SE of younger children with AccET increased over the first 4 years and then decreased thereafter. SE in eye with higher SE was tended to decrease significantly in patient with Acc ET than hyperopic control group (group × time p = 0.015). Amblyopic eyes showed a greater decreased in SE compared with non-amblyopic eyes, but it was not statistically significant (p = 0.07). SE was significantly decreased in children with more hyperopia (≥ 3 D) compared with children with less hyperopia (<3 D) (p = 0.008). Emmetropization of hyperopia was faster in hyperopic patients without AccET and could be affected by the age of the initial spectacles prescription, initial amount of SE, or presence of amblyopia.